Energy Management, Innovative Energy-Saving Technology, and BCG Model Influence on Gas Fuel-Saving Efficiency of Modern Industrial Factories in the Eastern Region - Sawatdikumthon, Thakon; Kongyoungyune, Rungraditt (Journal of Dhamma for Life, 2025)
This research aims to examine the influence of energy management, innovation management, and the implementation of the BCG (Bio-Circular-Green Economy) model on the effectiveness of gas fuel energy conservation in industrial factories located in Eastern Thailand. The study emphasizes the critical role of integrating energy management, innovation management, and the application of the BCG economic model to promote efficient energy usage, minimize energy loss, and reduce greenhouse gas emissions. The research employed path analysis to explore the structural relationships among the variables. Data were collected from 223 industrial factories using gas fuel. The statistical methods used included percentage, mean, standard deviation, and Pearson Product-Moment Correlation Coefficient. The findings revealed that energy management, innovation management, and the implementation of the BCG model had a statistically significant positive impact on energy conservation effectiveness. Particularly, effective energy planning and green economy support were identified as key factors. The analysis further indicated that energy management and innovation management exert both direct and indirect effects through the use of the BCG model, which emerged as the most influential factor in enhancing gas fuel energy conservation effectiveness among industrial factories in the eastern region of Thailand. Additionally, the adoption of circular economy and green economy concepts was found to reduce environmental impacts and enhance international competitiveness. The study recommends the development of policies that support technological innovation, encourage behavioral change in energy consumption, and promote collaboration between the public and private sectors to achieve sustainability in the industrial sector.